1997
DOI: 10.4012/dmj.16.60
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light Wavelength on Polymerization of Light-cured Resins

Abstract: Experimental light-cured composite resins were exposed to a narrow-band light at a constant quantum number using a narrow-band interference filter. The IR spectra of the cured resin specimens were measured before and after extraction of residual monomers. Degree of conversion (DC) and polymerization conversion (PC) were calculated from these IR spectra. The light in 410-550nm could be polymerized. With a brief exposure (5s), DC and PC were affected by the wavelength. The effect of wavelength between 410 and 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
121
0
30

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(152 citation statements)
references
References 17 publications
1
121
0
30
Order By: Relevance
“…As a consequence, more free radicals are generated and faster monomer conversion will occur, resulting in higher DC in shorter time (12). Some studies have suggested that halogen light still produce greater curing energy and higher degree of composite monomer conversion than the first generation of LED lights (7,8,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, more free radicals are generated and faster monomer conversion will occur, resulting in higher DC in shorter time (12). Some studies have suggested that halogen light still produce greater curing energy and higher degree of composite monomer conversion than the first generation of LED lights (7,8,13).…”
Section: Discussionmentioning
confidence: 99%
“…A great amount of unpolymerized monomers from Clearfil SE Bond adhesive were detected by FTIR analysis immediately after LED photo-activation. Regardless of the lower power density emitted by LED (7,8,13), differences in resin adhesive composition and sample preparation might have affected the DC when LED LCU was tested. The mixture of Bond and Primer of Clearfil SE Bond results in a solution with low pH (approximately 2) and high water content, which can impair the polymerization reaction of the adhesive.…”
Section: Discussionmentioning
confidence: 99%
“…The light intensity should be compatible with the absorption wavelength spectrum of the photoinitiator systems. For camphoroquinone, which is the most used photoinitiator system in dental composites, the maximum absorption peak is within the blue spectrum of visible light, about 468 nm (12). When similar energy densities are supplied to the composite resins, similar degrees of conversion and depth of polymerization will be obtained, regardless of the light-curing mode (9,10).…”
Section: Introductionmentioning
confidence: 95%
“…CQ is the photoinitiator most commonly used in dental composites. The maximum absorption peak fall within the blue band of visible light, at about 468 nm 18 . When the composite receives similar energy densities, similar degrees of conversion and polymerization depth will be obtained, regardless of the light-curing method.…”
Section: Introductionmentioning
confidence: 99%